The Effect of Financial Literacy and Digital Payment on Consumptive Behavior with Lifestyle as an Intervening Variable in Sukabumi City Students - Phytaloka, Ananda Dhea; Norisanti, Nor; Nurmala, Resa (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the effect of financial literacy and digital payment on consumptive behavior with lifestyle as a mediating variable among university students in Sukabumi City. Using quantitative approach and associative method, primary data were collected through questionnaires distributed to 240 respondents from six universities. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) to test direct and indirect relationships between variables. The results showed that financial literacy has a significant negative effect on consumptive behavior, while digital payment has a significant positive effect on consumptive behavior. In addition, lifestyle plays a significant role in mediating the relationship between financial literacy and consumptive behavior, as well as between digital payment and consumptive behavior. Students with a good level of financial literacy tend to have better self-control in consumption, while easy access to digital payments increases consumptive tendencies. This finding shows the importance of increasing financial literacy among students to form a wiser lifestyle, in order to reduce excessive consumptive behavior triggered by digital trends. This study provides practical implications for the campus and policy makers to develop financial education programs to equip students to face economic challenges in the digital era.